Dynamic damage characteristics of coal and rock mass under shock wave pulsating load - Xiankai BAO; Bin JIANG; Wu ZHANG; Xiangyu SONG; Jinchang ZHAO; Chaoyun YU; Tong ZHANG (Meitan kexue jishu)
To investigate the hydraulic load characteristics of high-voltage electric pulse shock waves in water, as well as the dynamic damage features of coal rock mass subjected to their influence, true triaxial fracturing tests on coal-rock specimens have been carried out. Under varied conditions of water pressure and discharge voltage, the investigation delved into attributes of water shock waves, including peak pressures, impulsive loads, and loading velocities. Elucidating the correlation between the circumferential effective stress at the drill hole periphery and the dynamic tensile strength of coal-rock mass. Furthermore, the study explored the relationships linking the initiation stress and propagation angle of cracks in coal-rock mass with factors such as in-situ stress, water pressure, and electric pulse shocks. Based on CT scans and the ABAQUS numerical simulation software,damage variables for coal rock mass with different hydraulic and electrical parameters were calculate and then evaluate the dynamic damage and crack initiation and propagation morphologies and evolutionary properties of coal rock mass. The results show that the peak pressure of the impulsive water shock increases rapidly with the amplification voltage and the water pressure, and the loading rate increases with the discharge voltage and decreases with the water pressure. Compared to the change in water pressure, the change in discharge voltage has a larger effect on the peak pressure of the water shock and its loading rate. The results of numerical simulations and laboratory tests are in good agreement and confirm each other from a microscopic point of view. The damage variables of the coal rock mass, the degree of damage and cracking significantly increase, and the number of cracks, length of extension, opening, and complexity change significantly with the water pressure and discharge voltage increase. Variations in the discharge voltage have a particularly marked effect on the destruction of coal rock mass. The research results can provide guidance for high electric pulse fracturing coal rock mass in water for efficient extraction of coalbed methane in China.